1986
DOI: 10.1002/bjs.1800730616
|View full text |Cite
|
Sign up to set email alerts
|

The clearance of 125I-labelled fibrin from the subcutaneous tissue of limbs with lipodermatosclerosis

Abstract: The clearance of radioactive fibrin from the subcutaneous tissues has been measured in the rat and in the limbs of normal subjects, patients with varicose veins, and patients with lipodermatosclerosis. The animal experiments showed that the most effective way of producing a subcutaneous deposit of fibrin was by the simultaneous injection of labelled fibrinogen and thrombin. The clearance of these clots was delayed when fibrinolysis was depressed with epsilon-aminocaproic acid. Clearance of subcutaneous fibrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In class 4 liposclerotic limbs, changes in the structure and also a decreased number of capillaries have been shown, 31 as well as increased leakage from these capillaries into surrounding tissue. 32 In limbs with severe CVD, studies have demonstrated the destruction of the superficial lymphatic plexus, 33 tissue hypoxia, [34][35][36] decreased fibrinolytic activity, [37][38][39] extravasation and pericapillary deposition of fibrin, [40][41][42] accumulation of other substances such as laminin, fibronectin, tenascin, and collagen, 43,44 and activation of leukocytes and endothelial cells, which leads to the degranulation of proteolytic enzymes and release of free radicals that damage the capillary wall. 45,46 Local skin dysfunction could also be attributed to the collagen deposition from fibroblasts that have been activated through leukocytes that release active transforming growth factor-β 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In class 4 liposclerotic limbs, changes in the structure and also a decreased number of capillaries have been shown, 31 as well as increased leakage from these capillaries into surrounding tissue. 32 In limbs with severe CVD, studies have demonstrated the destruction of the superficial lymphatic plexus, 33 tissue hypoxia, [34][35][36] decreased fibrinolytic activity, [37][38][39] extravasation and pericapillary deposition of fibrin, [40][41][42] accumulation of other substances such as laminin, fibronectin, tenascin, and collagen, 43,44 and activation of leukocytes and endothelial cells, which leads to the degranulation of proteolytic enzymes and release of free radicals that damage the capillary wall. 45,46 Local skin dysfunction could also be attributed to the collagen deposition from fibroblasts that have been activated through leukocytes that release active transforming growth factor-β 1 .…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt of the existence of the fibrin cuffs themselves, as they have been observed in a number of histological studies [71,72]. There is also little doubt that there is reduced fibrinolytic activity in patients with chronic venous insufficiency [73][74][75][76]. A commercially available fibrin membrane of 1 mm thickness has been shown to delay the diffusion of oxygen [71 ].…”
Section: Abnormalities Of Capillary Blood Flow and Morphology And Thmentioning
confidence: 99%